Implications of the Marginalisation of Social Sciences in the Fight against the Covid 19 Pandemic: A Humanities Perspective - Mathew, Tirivangasi Happy; Louis, Nyahunda; Mabila, Thembinkosi E.; Mugambiwa, Shingirai Stanely (International Journal of Criminology and Sociology, 2021)
In the history of pandemics that plagued humanity, COVID-19 represents a catastrophic global health crisis. The pandemic has placed a huge burden on health care systems around the globe. Due to its easy transmission from one individual to the other, COVID-19 prevention require large scale behaviour change. Through the recommendations of the WHO, governments across the world have enacted policies of social distancing, national lockdown, wearing face mask, release of inmates from prisons, temporary citizenship to migrants and refugees. In fostering the contingent measures to manage the pandemic between March and December 2020, most governments have consulted epidemiologists, public health experts, virologists among other pure sciences disciplines. However, notably absent, or poorly represented were the insights from social and behavioural scientists. The researchers argue that the absence or marginalisation of social sciences in the battle against the pandemic creates a myriad of gaps among the mechanisms crafted to manage the pandemic. The aim of this paper is to provide the entry points of social scientists in the fight against the pandemic. Through the use of insights of sociology and social work disciplines, the researchers noted that social scientists are involved in behaviour modification, compacting fear and anxiety, promotion of human rights, psychosocial support to vulnerable populations; and understanding the pandemic in the scope of globalisation. In terms of recommendations, we suggest that social workers and sociologists need to depend on the repertoire of their disciplines in order to effect change in different communities during the pandemic and its aftermath.